2021
DOI: 10.25115/eea.v40i1.4525
|View full text |Cite
|
Sign up to set email alerts
|

Constituting A Root Map Towards Inclusive Growth: A Comparative Analysis

Abstract: Developing and emerging countries of Asia have shown a tremendous improvement in economic growth rates couple with the significant strides in extreme poverty reduction. However, most of the economies are still facing some challenges like income and non-income disparities in sharing benefits and participation into social and economic activities. It requires attention that economic growth must be accompanied by reduction in poverty and income & non-income inequalities, and promoting equitable participation, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(4 citation statements)
references
References 0 publications
3
1
0
Order By: Relevance
“…In terms of the different dimensions of globalization, political globalisation presents a greater chance of attaining broad inclusive growth followed by social globalisation whereas economic growth globalisation has the least effect. Our results are consistent with the findings in prior studies such as Heimberger (2020), Daly et al (2017), Duttagupta et al (2018), Shahzad and Chaudhary (2020), de Barros Santiago (2017), Yameogo et al (2021), Asongu et al (2020), Bataka (2019), Gygli et al (2019), Quinn et al (2011), Le and Ozturk (2020), Asongu and Odhiambo (2020) and Zaidi et al (2019). What the results portend is that globalisation and particularly economic globalisation can facilitate international exchanges (transfer) and interaction of resources, foreign trade, technological transfers and increment in manufacturing and productivity in Africa.…”
Section: Empirical Results and Discussionsupporting
confidence: 94%
See 3 more Smart Citations
“…In terms of the different dimensions of globalization, political globalisation presents a greater chance of attaining broad inclusive growth followed by social globalisation whereas economic growth globalisation has the least effect. Our results are consistent with the findings in prior studies such as Heimberger (2020), Daly et al (2017), Duttagupta et al (2018), Shahzad and Chaudhary (2020), de Barros Santiago (2017), Yameogo et al (2021), Asongu et al (2020), Bataka (2019), Gygli et al (2019), Quinn et al (2011), Le and Ozturk (2020), Asongu and Odhiambo (2020) and Zaidi et al (2019). What the results portend is that globalisation and particularly economic globalisation can facilitate international exchanges (transfer) and interaction of resources, foreign trade, technological transfers and increment in manufacturing and productivity in Africa.…”
Section: Empirical Results and Discussionsupporting
confidence: 94%
“…This suggests that liberalisation does not provide inclusiveness. This is corroborated, to some extent, by the study conducted by Shahzad and Chaudhary (2020) for some selected Asian countries. Specifically, Shahzad and Chaudhary (2020) concluded that some components of globalisation have negative effects on inclusive growth, particularly ethnic diversity and environmental distortions.…”
Section: Theoretical and Empirical Literature Reviewsupporting
confidence: 69%
See 2 more Smart Citations